Football and Dementia: Understanding the Link - Neal, James; Hutchings, Paul B.; Phelps, Ceri; Williams, Donald (Frontiers in Psychiatry, 2022)
Football, also known as soccer or association football, is popular but is linked with dementia developing in retired players. Controversy exists whether this dementia is caused by heading the ball, a form of mild repetitive traumatic brain injury (rTBI), over many years. North American Football (NFL) is a very different game with frequent collisions. Substantial data exist showing that many ex-NFL players develop a specific dementia: chronic traumatic encephalopathy (CTE), the neuropathological disorder of boxers. In Britain evidence for the neuropathological basis of footballers’ dementia has been slow to emerge. A 2017 study revealed that of six ex-soccer players four had CTE with Alzheimer’s disease (AD) and two had AD. A 2019 study showed that ex-footballers were 3.5 times more likely to die from dementia or other neuro-degenerative diseases than matched controls. We argue that the vulnerability of the brain to heading a football is predicated on its disproportionate size and extreme fragility due to its semi-solid structure. In childhood and adolescence this instability is increased because of the slow myelination and maturation processes which are not completed until early adulthood. Two firm recommendations are made: (i) no heading below the age of 16; (ii) amateur and professional players should undergo regular psychological testing to detect early cognitive impairment. Clinical psychologists and psychiatrists interested in the prevention and treatment of dementia will be at the forefront of managing this emerging public health challenge.